EKSEPSI DALAM PERKARA PIDANA - Didik Endro Purwoleksono (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2003)
In criminal crises, defendants or their legal counsellors have chances to file exceptions. The definition of exception is as defence means to avoid from decisions on main cases, as by way of receiving evasions well, determination on, main cases is not needed anymore. Such exceptions are filed whenever there are reasons that a court is not authorized to put their cases on trial; indictment is unacceptable; indictment is Exceptions that result in indictment is unacceptable; indictment is overruled for the sake of laws. Exceptions that result in indictment stated is annual led, such indictment can still be opened again.